UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENYUSUN RPP MELALUI PELATIHAN SIMULASI DI SMP NEGERI 3 TAMBANG TAHUN 2021 - M.Arianto (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
Professional teachers must have 4 competencies, one of which is program preparation, namely preparing lesson plans to prepare materials to be used in the learning process. This is stipulated in Government Regulation Number 19 of 2005 concerning National Education Standards and Permendiknas Number 16 of 2007 concerning Standards of Qualification and Academic Competence of Teachers, and Permendiknas Number 10 of 2009 concerning Certification of Teachers in Position, and Permendiknas Number 41 of 2007 concerning Process Standards. In reality, most teachers have difficulty in preparing lesson plans. One of the reasons: 1.There are 4 teachers who make lesson plans and have implemented them in their schools; 2. There are 5 teachers who have participated in the RPP preparation training but have not been able to implement it in their schools; 3. There are 11 teachers who have never attended training in the preparation of lesson plans, they only copy paste to their colleagues. This condition, of course, cannot be allowed to continue, but there must be a solution or real action from the principals. In this regard, teachers must be fostered and facilitated to improve their ability to prepare lesson plans. Efforts to improve the ability of teachers in preparing lesson plans can actually be done in various ways, including through training, involving teachers in seminars and workshops, providing various guides and modules, workshops, and various other efforts. However, considering all the advantages and disadvantages, simulation training is more appropriate. The consideration is that with a teacher simulation, the teacher is more proactive and forms self-character in an effort to develop lesson plans. In connection with the foregoing, the research problem can be formulated in the form of research questions: “Can training in the preparation of lesson plans improve the performance of teachers at SMP Negeri 3 Tambang, Kampar Regency? This problem-solving plan is carried out by training in the preparation of RPP simulations for teachers at SMP Negeri 3 Tambang, Kampar Regency to improve teacher performance. As for making these decisions, the basic competencies required in the KTSP. In line with the problems above, the main objective in preparing the RPP is to assist the teachers of SMP Negeri 3 Tambang in compiling the RPP so that it can be a reference in the learning process, so that minimum completeness can be achieved. This action is expected to be useful for teachers of SMP Negeri 3 Tambang. First, it provides great benefits in solving teacher problems in preparing lesson plans. Second, the teacher prepares himself before the learning process takes place. Third, the ability of teachers to increase their ability to carry out the preparation of lesson plans. Fourth, the ability of teachers and the ability of students in schools is ensured that the quality of learning increases. This research requires references that are relevant to the concepts, principles, and procedures for implementing school action research, such as books and journals on research topics in general that are directly related to action research. In addition, it is also necessary to conduct a literature review on RPP, such as the position, main tasks, functions, roles, and programs and performance that can be carried out by teachers. Furthermore, it is also necessary to conduct a study of the possible impacts that can be obtained from empowering teachers in schools. This research was conducted at SMP Negeri 3 Tambang Kampar Regency, the number of teachers involved was 20 teachers. The implementation of this research is preceded by preparation in the form of activity scenarios, time and place schedules, necessary resource persons, other supporting facilities, such as learning resources, observation sheets, assessment rubrics, and proposals, as well as school research reports made. This action research introduces the empowerment of teachers at SMP Negeri 3 Tambang, Kampar Regency with the following implementation steps. Along with the implementation of teacher empowerment activities, observations are made on the process and progress and other results. For this purpose, the researcher carried it out himself with the help of observation sheets and rubrics, which were prepared in advance. At the end of the activity, an evaluation was carried out in the form of a proposal presentation forum and a brief report on the results of the research, by asking for help from reviewers from resource persons. Based on the results obtained during the process of teacher empowerment activities and the results of the evaluation carried out, it will be followed by reflection, to find positive things and negative things that still need improvement. This research was carried out in two cycles. In the first cycle, the researcher carried out the actions as described in the preparation and plan above. In the second cycle, the lesson plans are revised based on the results and findings in the first or previous cycles. As a final conclusion, this school action research activity is as follows: (1) The role of school supervisors in fostering n is very much needed in motivating the teachers of SMP Negeri 3 Tambang to improve their performance as seen in the results of the research cycle 1 to cycle 2, the teacher's performance has increased very significantly. (2) The ability of the teachers of SMP Negeri 3 Tambang Kampar Regency has increased in the preparation of lesson plans. From cycles 1 and 2 there was an increase since the initial data collection, due to the motivation to take part in training and preparation of lesson plans. (3) The level of knowledge and understanding of teachers about the implementation of preparation of lesson plans in cycle 1 was still weak, but after cycle 2 all teachers amounted to 20 teachers already has a performance in the good category. Based on the results of school action research, the following can be recommended: 1. The role of school supervisors in providing guidance for teachers of SMP Negeri 3 Tambang is very much needed and can be carried out continuously and programmed either through training or similar activities, namely workshops or simulations. 2. It is a must for teachers to prepare lesson plans before carrying out learning activities so that the completeness of SK and KD to achieve KKM can be achieved